Advanced Imaging of the Scapula: What Every Radiologist Needs to Know. Issue 4 (July 2016) - Mazaheri, Parisa; Fayad, Laura M.; Fishman, Elliot K.; Demehri, Shadpour
Abstract : Abstract: The scapula plays a central role in shoulder motion and stability. A wide variety of anatomic variants as well as traumatic, neoplastic, and infectious pathologies can involve the scapula. Detection of scapular lesions using radiography can be challenging because of the obscuration by the overlying structures or incomplete imaging during shoulder magnetic resonance imaging or computed tomography examinations. Familiarity with imaging characteristics of these abnormalities will allow radiologists to better diagnose and characterize scapular disorders.